CORRELATIVE CONNECTORS IN ORALITY CONTEXTS:: FUNCTIONAL PRODUCTIVITY THROUGH GRAMATICALIZATION (PERcursos Linguísticos, 2022)
This paper consists of a section from a broader research, which investigates correlative connectors, looking for evidence that the correlation is about a syntactic and discursive process distinct from the traditional dichotomy: coordination / subordination. The data under analysis comes from the spoken language modality, collected in the D&G corpus in the city of Natal, Rio Grande do Norte. We oppose the treatment that representatives of traditional grammar address to the theme with more recent analyzes developed by researchers affiliated with functionalist linguistic approaches. To explain, from a functionalist optics, the constitution of the formation processes of correlative peers, we apply principles of grammaticalization of Hopper (1991). For conclusion, we defend that the correlation is a phenomenon in emergence, noting the productivity of new peers or the transformation of peers already consolidated by uses.